Diagnostic Utility of NT-Pro BNP in Elderly Patients Presenting With Acute Dyspnea in Emergency Department - Shrestha, Manoj; Bhusal, Pramod (Journal of National Heart and Lung Society Nepal, 2023)
ABSTRACT BACKGROUND: Acute dyspnea may be related to lungs pathology or cardiac pathology or due to involvement of both. Rapid diagnosis of the cause of dyspnea in emergency can help in early start of treatment preventing further progress of the symptoms, prolong hospital stay, need of more invasive medical procedures like intubation and ventilation thereby decrease the morbidity and mortality of the patients. METHODOLOGY: The study was conducted for three months i.e, from 16th May 2023 till 17th August 2023. 150 patients fulfilling inclusion criteria were taken. Clinical diagnosis in these patients was established based on medical history as well as echo and chest X-ray. Based on their clinical diagnosis, the patients were divided into three groups: group A diagnosed with pulmonary dyspnea (PD), group B diagnosed with congestive heart failure (CHF), and group C diagnosed with combined dyspnea (CHF+PD). NT-proBNP level in these patients was measured and compared. RESULTS: The study population constituted 60% males and 40% female with mean age of 68.9±10.99. Out of 150 patients presenting with acute dyspnea in emergency department, 65 patients were diagnosed with congestive heart failure, 55 patients were diagnosed with pulmonary dyspnea and 30 patients diagnosed with combined dyspnea. Average NT-proBNP among group A patients was (1300±175) ng/l, among group B patients was (275±70) ng/l and among group C patients was (1276±165) ng/l. CONCLUSION: NT-proBNP is the reliable marker to differentiate the cardiac and pulmonary causes of acute dyspnea among elderly patients presenting to emergency. KEY WORDS: N-terminal pro-B-type natriuretic peptide (NT-proBNP), emergency, elderly patients, dyspnea, biomarker